Constitutive Parliament and its speakers - Algis Kasperavičius (Lietuvos Istorijos Studijos)
On April of 1920, elected Constitutive Parliament term continued till the 6th of October 1922. It worked strenuously; there took place 257 ordinary meetings, which continued for some hours every day. They often ended in the next morning. The most important task of the Constitutive Parliament was to prepare a permanent Constitution of the Lithuanian Republic, but it performed other rules' publishing functions too. It performed the control of executive government institutions of all levels. The education of parliament members was much better than the middle education of Lithuanian citizens, but most of them didn't have university education. However, it wasn't a big imperfection of the just born parliamentary system of Lithuania. A diploma or an academic degree isn't identical to the broad mind and the knowledge necessary for political leaders. It can be acquired in the way of self-education too. Oratorical skills are very important as well.